2011
DOI: 10.1007/s10461-011-9975-1
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Efficacy of Two Interventions to Reduce HIV Risk Behaviors Among Drug Users

Abstract: Numerous interventions have been developed and implemented to decrease risk behaviors which lead to HIV infection and transmission. These interventions have been differentially successful in reducing high risk behaviors in various populations. Testing and evaluation of the interventions have been subject to various degrees of rigor. The CDC recommends the use of interventions which have been rigorously tested and meet the standards for evidence based intervention rather than the continuation of the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…7,8 The Centers for Disease Control and Prevention (CDC) recommends the comparison of new interventions with others also found to be effective. 9 Randomized controlled studies on the effectiveness of HIV prevention and long-term evaluations are scarce in Spain. 10 Randomized controlled studies are needed to evaluate the longterm effectiveness of programs promoting the sexual health of Spanish youths.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 The Centers for Disease Control and Prevention (CDC) recommends the comparison of new interventions with others also found to be effective. 9 Randomized controlled studies on the effectiveness of HIV prevention and long-term evaluations are scarce in Spain. 10 Randomized controlled studies are needed to evaluate the longterm effectiveness of programs promoting the sexual health of Spanish youths.…”
Section: Introductionmentioning
confidence: 99%
“…Costa Rica female sexual workers showed that acceptability in the use of female condom would allow them empowerment over sexual relationships, yet today it is not available for the population (Madrigal, Schifter, & Feldblum, 1998). Prevention strategies, if implemented, should focus not only in providing concrete scientifically based information, but also in providing prevention strategies proven to work (Booth, Lehman, Dvoryak, Brewster, & Sinitsyna, 2009;McCoy, De Gruttola, Metsch, & Comerford, 2011;Stacy et al, 1999;Williams et al, 2011) Research on drug users out of the clinical treatment condition is not considered by health authorities in the HIV/AIDS prevention context. Current HIV National Strategic Plan 2011-2015 (Ministerio de Salud, 2010b) recognizes drug users as an important vulnerable group; however, they plan only to advise the promotion of prevention campaigns among adolescents in context of treatment conditions at the National Institute on Alcoholism and Drug Dependence (IAFA).…”
Section: Discusionmentioning
confidence: 99%
“…Behavioral prevention strategies may include attempts to delay onset of first intercourse and/or decrease the number of partners where epidemics have become generalized [19-21], sometimes referred to as primary behavior change [22]. In a broader view, behavioral interventions aim to increase the proportion of protected sex acts [23, 24], provide counseling and testing [25, 26], encourage adherence to antiretroviral therapy [27, 28], and decrease substance use or mitigate its risks [29-31]. Strategies may attempt to motivate behavioral change within individuals through education, motivational activities, skills building and community normative approaches.…”
Section: Social and Individual Behavior In The Hiv Epidemic And Prevementioning
confidence: 99%